2013
DOI: 10.1016/j.jacc.2013.05.078
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Age-Related Interstitial Myocardial Fibrosis With Cardiac Magnetic Resonance Contrast-Enhanced T1 Mapping

Abstract: Objectives This study sought to determine the relationship of cardiovascular magnetic resonance (CMR) measures of tissue composition to age in the Multi-Ethnic Study of Atherosclerosis (MESA). Background Animal and human studies have demonstrated increased collagen deposition in senescent hearts. New CMR indices of tissue composition by using T1 mapping are sensitive to the presence of myocardial fibrosis. Methods A total of 1,231 study participants (51% women; age range 54 to 93 years) of the MESA cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
249
5
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(280 citation statements)
references
References 47 publications
23
249
5
3
Order By: Relevance
“…[27] Second, the T1 may have been abnormal in these patients prior to myocardial infarction, due to discrete microscopic fibrosis caused by comorbidities such as diabetes, hypertension or hypercholesterolemia. [30,31] In order to establish which hypothesis is correct, our findings would have to be validated through histology. Given that our proposed ROC-derived threshold is free from any assumptions regarding remote myocardium, we believe it is more appropriate than T2W imaging for delimiting myocardial oedema in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Second, the T1 may have been abnormal in these patients prior to myocardial infarction, due to discrete microscopic fibrosis caused by comorbidities such as diabetes, hypertension or hypercholesterolemia. [30,31] In order to establish which hypothesis is correct, our findings would have to be validated through histology. Given that our proposed ROC-derived threshold is free from any assumptions regarding remote myocardium, we believe it is more appropriate than T2W imaging for delimiting myocardial oedema in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In general, linear regression analyses demonstrated that a greater partition coefficient, native T1 values and ECV were associated with older age in men (multivariate regression coefficients=0.01; 5.9 ms; and 1.04% per 10 year change; all p<0.05). ECV was also significantly associated with age in women after multivariate adjustments [15]. In another MESA study, 25-minute post-gadolinium T1 time showed more statistically significant associations with cardiovascular disease risk scores (10/14 scores, 71%) compared to other cardiac magnetic resonance (CMR) imaging indices (e.g., native T1; 7/14 scores, 50%) and the partition coefficient (7/14, 50%) in men [17].…”
Section: Risk Stratification In the General Population Normal Values mentioning
confidence: 95%
“…With MOLLI sequencing, which is the most popular T1 mapping sequence, normal myocardial native T1 ranges from 950 to 982 ms and thereby ECV is 25.0 to 26.9% in a 1.5 T magnetic field [5,6,14,15]. In a 3 T magnetic field, native T1 is somewhat prolonged to 1052 to 1159 ms [6,16].…”
Section: Risk Stratification In the General Population Normal Values mentioning
confidence: 99%
See 2 more Smart Citations